Model of inactivation of Campylobacter jejuni in scalding of chicken process - Osiriphun, Sukhuntha; Tuitemwong, Pravate; Koetsinchai, Woranut; Tuitemwong, Kooranaee; Erickson, Larry E. (My University, 2012)
The purpose of this study was to develop a model of inactivation of Campylobacter jejuni in industrial scalding of chickens. Models can be used as a guide for broiler slaughterhouse operations for reducing levels of C. jejuni contamination on broiler carcasses. Mean concentrations of C. jeuni in terms of colony farming units (CFU) in scald tank water and in carcass rinse solution after scalding were 2.90±0.07 and 3.86±0.11 LogCFU/ml, respectively. Scald tank water temperature, flow rate, pH, and total solids in scalding process water were 54.15±0.2°C, 172.0±8.4 L/min, 8.0±0.01, and 2,565±114.3 mg/L, respectively. Inactivation models were developed by using literature data for inactivating kinetics, of Campylobacter and the Arrhenius equation. Results of the inactivation models of scalding process indicated that high temperature and short time (less than 2 minutes) of scalding process were effective in reducing the number of viable cells. The model fits the experimental data well and the values of the estimated parameters provide insight for this process. The model can be used for process design and potential process modifications.
Model of inactivation of Campylobacter jejuni in poultry scalding
Keywords: Campylobacter; Scalding; Inactivation; Chickens; Model